The Treatment of Elderly Patients With Acute Myeloid Leukemia - Krug, Utz (Deutscher Arzte Verlag, 2011)
BACKGROUND: In patients over age 60 with acute myeloid leukemia (AML), cure rates are under 10% despite intensive chemotherapy. These patients often have comorbidities, and their treatment must be chosen with care. For those who are not candidates for intensive chemotherapy, one of the available options for palliative treatment should be chosen on the basis of an individual risk-benefit assessment. METHODS: Selective literature review. RESULTS: An evaluation of the patient’s general condition and comorbidities, a geriatric assessment, and specially designed risk scores are useful aids to the choice of an appropriate treatment. Some elderly patients with AML can benefit from intensive chemotherapy despite their age; for highly selected elderly patients, allogeneic stem-cell transplantation is an increasingly feasible option. Hypomethylating agents or low-dose cytarabine can be suitable for some patients. Further options include experimental treatment as part of a clinical trial, and supportive care alone. In the special case of acute promyelocytic leukemia, more than half of all patients can be cured with combination chemotherapy including all-trans retinoic acid. CONCLUSION: The prognosis of elderly AML patients remains poor despite recent therapeutic advances. The appropriate treatment for each patient can be chosen on the basis of a risk-benefit assessment. Clinical trials evaluating new treatments are urgently needed.